2003
DOI: 10.1590/s0066-782x2003001400001
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of hypertension in chronic Chagas' disease: retrospective clinical study

Abstract: Chagasic patients had a frequency of hypertension similar to that of the general population, and the clinical profile of the hypertensive chagasic patients seemed not to differ a lot from that of the chagasic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
2
10
0
1
Order By: Relevance
“…Systemic arterial hypertension can affect about 30% of inhabitants in areas where Chagas' disease is endemic 11 and it may also compromise about 33% of Chagas' disease patients 12 . Chronic heart failure can affect 8% of patients with both conditions 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Systemic arterial hypertension can affect about 30% of inhabitants in areas where Chagas' disease is endemic 11 and it may also compromise about 33% of Chagas' disease patients 12 . Chronic heart failure can affect 8% of patients with both conditions 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Guariento et al aimed to define the association between Chagas disease and primary arterial hypertension and concluded that, when associated, cardiac compromise was more frequent and serious, this association being more prevalent in the elderly 17 . Gurgel et al retrospectively studied 225 hypertensive patients with Chagas' disease to verify the frequency of SAH in that group, and found similarity with the population in general 9 . In a clinical and anatomopathological study, Gurgel and Almeida also evaluated the frequency of SAH in patients with Chagas' disease, obtaining similar results to the previous study and concluding that the association of the 2 illnesses did not alter the natural history of either 8 .…”
Section: Ethical Considerationsmentioning
confidence: 97%
“…Overall variation in blood pressure before and after the exercise program, during wakefulness and sleep were described in Figures 1, 2, and 3, respectively. The damage to the autonomic nervous system stands out amongst the alterations described in chronic Chagas' heart disease, with a predominance of dysfunction of the parasympathetic system 14,15 , enabling sympathetic system activity, which could contribute to the development of arterial hypertension 8,9 . On the other hand, the action of physical exercise attenuating sympathetic activity 15,16 has been described, which make it necessary a study on the effect of physical exercise on the variation of blood pressure in this group of people.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations